Experience in research and injection of flue gases into oil fields to increase oil recovery - C. A. Garifullina; T. F. Khaliullin; I. M. Indrupskiy; I. V. Valiullin; A. A. Zalyatdinov; E. A. Burlutskiy; R. Kh. Sadreeva; R. R. Aflyatunov; I. Kh. Kashapov (Georesursy, 2024)
Decreasing negative impact of industrial emissions to the atmosphere and prolonging fossil fuel usage period are urgent issues of fuel and energy sector. In view of this problem, injection of flue gases into oil fields to increase oil recovery may be considered as environmentally safe and economically rational way for beneficial use of greenhouse gas emissions. To effectively displace oil with flue gases it is important to consider many factors: influence of composition of the flue gases and oil, miscibility conditions, injection regimes, etc. Flue gases, a product of fuel combustion in air, can be produced as a result of oil self-ignition when air is injected into a reservoir with light oil (thermal gas method). Flue gases from natural gas, fuel oil or coal combustion in power plants or other processes that burn fossil fuels can also be used for injection into the reservoir. This paper presents an analysis of the world laboratory and industrial experience in studying efficiency of oil displacement using flue gases. Conclusions are presented about optimal criteria for implementation of this process and directions for further research.